Adverse effects of vitamin D deficiency on the Pi3k/Akt pathway and pancreatic islet morphology in diet‐induced obese mice. Issue 2 (26th October 2015) - Borges, Celina Carvalho; Salles, Andreza Fernandes; Bringhenti, Isabele; Souza‐Mello, Vanessa; Mandarim‐de‐Lacerda, Carlos Alberto; Aguila, Marcia Barbosa
Abstract : Scope: To investigate the impact of vitamin D deficiency on insulin resistance and abnormal glucose homeostasis in obesity. Methods and results: Sixty male C57BL/6 mice (3 months old) were fed a control diet (C—10% energy as fat) or a high‐fat diet (HF—50% energy as fat), with or without vitamin D, for 8 weeks. There was no difference in body mass between the HF and HF/VitD‐ groups. Vitamin D deficiency (VitD) in the diet‐induced obese mice increased hyperinsulinemia ( p = 0.04), hyperleptinemia ( p = 0.0002), insulin resistance (HOMA‐IR, p = 0.04), and islet changes, including alpha and beta cell disarray. In the insulin signaling pathway, insulin receptor substrate 2 expression was upregulated in the C/VitD‐ group ( p = 0.001) and downregulated in the HF/VitD‐ group ( p = 0.009). Interestingly, forkhead box protein O1 expression was higher in the HF/VitD‐ group than in the HF group ( p = 0.03), and pancreatic and duodenal homeobox 1 expression was lower in the HF/VitD‐group than in the HF group ( p = 0.025), indicating that the HF diet and vitamin D deficiency influenced the downregulation of the expression of these proteins (two‐way ANOVA, p < 0.0001). Conclusion: Vitamin D deficiency exacerbated the adverse structural and physiological remodeling of pancreatic islets due to obesity, contributing to abnormal glucose homeostasis.